Asymmetric Exchange Rate Pass-Through in Southeast Asian Rice Trade. (2nd August 2021) - Wiseman, Taylor; Luckstead, Jeff; Durand-Morat, Alvaro
Abstract: Asian countries consume approximately 90% of the world's rice supply. Between 2007 and 2014, Thailand, Vietnam, and India accounted for 60% of the world's exports of rice. A nonlinear autoregressive distributed lag (NARDL) econometric model is utilized to estimate the impact of exchange rate fluctuations on rice trade in Southeast Asia. Focusing on the largest importing countries and exporting country by volume, the analysis considers Malaysian, Indonesian, the Philippines, and Chinese rice imports from Thailand. Results show that importing countries' state trading enterprises (STEs) generally do not follow profit-maximizing behavior in reacting to exchange rate volatility.